THE INFLUENCE OF SEMEN FREQUENCY COLLECTION ON CONCENTRATION AND SPERMATOZOA ABNORMALITIES OF QUAIL - Bebas, Wayan; Permana, Komang Gita; Trilaksana, I Gusti Ngurah Bagus; Laksmi, Desak Nyoman Dewi Indira (Buletin Veteriner Udayana, 2018)
The aims of this study are to determine the influence of collecting frequency against concentration and spermatozoa abnormalities of quail. This study used a completely randomized design (CRD) with 3 treatment groups, is collecting sement at 2, 3 and 4 days intervals. Each treatment is repeated 9 times. Observations were made on the concentration of spermatozoa (10 7 cells/ml) and abnormalities of spermatozoa (%). The data were analyzed using analysis of variance (ANOVA) if there are significantly different (P<0.05) followed by Duncan test. The results showed the concentration of spermatozoa in each treatment respectively 39.00±5.148 x10 7 cells/ml; 59.49±1.878 x10 7 cells/ml; 59.11±2.028 x10 7 cells/ml. Abnormality in each treatment was 14.22±1.394%; 7.22±1.202%; 7.49±1.130%. The frequency of ejaculation was statistically significant (P<0.05) against the concentration and spermatozoa abnormalities of quail.